2018
DOI: 10.1016/j.heliyon.2018.e00898
|View full text |Cite
|
Sign up to set email alerts
|

Acute benzo[a]pyrene treatment causes different antioxidant response and DNA damage in liver, lung, brain, stomach and kidney

Abstract: Acute effects of oxidative damage induced by benzo[a]pyrene (B[a]P) on various organs are still not clear. In this study, we investigated oxidative stress and DNA damage in liver, lung, stomach, brain and kidney of ICR male mice induced by acute B[a]P treatment. B[a]P treatment led to a significant decrease at the different doses in body weight. For the variations of superoxide dismutase (SOD), catalase (CAT), glutathione S-transferase (GST), glutathione (GSH) and GSH/GSSG, significant increases were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 52 publications
5
27
1
Order By: Relevance
“…PM2.5 group in the lungs . Deng et al discovered that the liver histology remained almost normal with 50 mg/kg BaP treatment on mice when compared with the control, while there was the thickening alveolar wall, compressed alveolar and severe inflammatory cells infiltration phenomenon in lung . These results were consistent with the present study, suggesting that the pathologic changes of lung were more obvious than that of liver when treated with Phe in female rats.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…PM2.5 group in the lungs . Deng et al discovered that the liver histology remained almost normal with 50 mg/kg BaP treatment on mice when compared with the control, while there was the thickening alveolar wall, compressed alveolar and severe inflammatory cells infiltration phenomenon in lung . These results were consistent with the present study, suggesting that the pathologic changes of lung were more obvious than that of liver when treated with Phe in female rats.…”
Section: Resultssupporting
confidence: 91%
“…Deng et al found that a significant increase of SOD at 24 hours, then decreased till 72 hours, while MDA was significantly increased in a time‐ and dose‐dependent increase manner after acute BaP injection in mice, and the results suggested that BaP induced relative high oxidative stress in liver and lung . Another study exhibited that SOD activity was increased between 4 hours and 18 hours, but decreased at 24 hours, while MDA content was increased when rats were exposed to diesel engine exhaust .…”
Section: Resultsmentioning
confidence: 98%
“…Consistently, observations from this study demonstrated that a single administration of B(a)P to mice resulted in lung injury at morphological and histological levels. The elevation of pro-inflammatory cytokine levels in the blood samples was consistent with previous reports that showed B(a)P-induced deleterious consequences in multiple organs [ 41 , 45 ]. Moreover, oral supplementation of jujube extracts, both HJE and NHJE, reduced levels of NF-κB and its downstream cytoplasmic proteins, iNOS and COX-2, in the lungs while increasing expressions of Nrf2 and cytoplasmic HO-1 in lung and liver tissues.…”
Section: Discussionsupporting
confidence: 91%
“…Benzo[a]pyrenediol-epoxide, which is metabolized from B(a)P by cytochrome P450 enzymes, provokes pulmonary inflammation by stimulating the NF-κB-mediated pathway in human lung fibroblasts [ 42 ]. Thus, B(a)P is widely used to generate a lung inflammation in mice [ 43 , 44 , 45 ]. Consistently, observations from this study demonstrated that a single administration of B(a)P to mice resulted in lung injury at morphological and histological levels.…”
Section: Discussionmentioning
confidence: 99%
“…In Fish, hepatic phase I and II metabolism including biotransformation enzymes and the cytochrome P450 (CYP) superfamily are the major pathway for the biotransformation of the B[a]P and other PAHs [11,12]. During the biotransformation of B[a]P that dominates toxicokinetics, carcinogenic metabolites are produced and may reach higher concentrations in organisms than their parent compounds [13,14]. Also, Reactive oxygen species (ROS) are continuously generated in this process [15,16].…”
Section: Introductionmentioning
confidence: 99%